Unintentional injuries and potential determinants of falls in young children: Results from the Piccolipiù Italian birth cohort - Martina Culasso; Daniela Porta; Sonia Brescianini; Luigi Gagliardi; Paola Michelozzi; Costanza Pizzi; Luca Ronfani; Franca Rusconi; Liza Vecchi Brumatti; Federica Asta (PLoS ONE, 2022)
Objectives Unintentional injuries such as falls, are particularly frequent in early childhood. To date, epidemiological studies in this field have been carried out using routine data sources or registries and many studies were observational studies with a cross-sectional design. The aims of the study are to describe unintentional injuries in the first two years of life in the Piccolipiù birth cohort, and to investigate the association between mother and children characteristics and the First Event of Raised surface Fall (FERF). Methods This longitudinal observational study included 3038 children from an Italian birth cohort. Data on socio-demographic factors, socio-economic indicators, maternal health and lifestyle characteristics and child’s sleeping behavior, obtained from questionnaires completed at birth, 12 and 24 months of age, were considered in the analyses as potential risk factors of FERF. Time of occurrence of FERF was analyzed using the Kaplan-Meier method. The multivariable analysis for time to event was carried out using a Cox proportional hazards model. Results Falls from raised surfaces are the leading cause of unintentional injuries in the cohort with 610 (21.1%) and 577 (20.0%) cases among children during the first and second year of life, respectively. An increased risk of FERF was associated with several risk factors: maternal psychological distress (HR 1.41, 95%CI 1.10–1.81), maternal alcohol intake (HR 1.26, 95%CI 1.10–1.45), and child’s sleeping problems (HR 1.28, 95%CI 1.09–1.51). Children with older aged mothers (HR 0.98, 95%CI 0.96–0.99) and living in northern Italy (HR 0.64, 95%CI 0.55–0.75) had a lower risk of FERF. Conclusion The results of the study suggest that a higher risk of FERF is associated with socio-demographic factors, maternal characteristics and child sleeping behavior that could hinder parent empowerment.